Teachers’ Attitudes Towards Dealing with Controversial Issues in the EFL Classroom: A Pilot Study - Divéki, Rita (Working Papers in Language Pedagogy, 2018)
The main aim of this small-scale questionnaire study involving 35 participants was to validate a research instrument which is to be used in the author’s main study on Hungarian EFL teachers’ attitudes towards the incorporation of controversial issues (CI) into their lessons. The other aims of the study were to reveal how often teachers teach CI, what CI they teach, what background variables influence their decisions to teach CI and what stance they take when dealing with CI in class. After an extensive review of literature on global education and teaching controversial issues, some insight is given into the validating process and some preliminary results are provided regarding the research questions. Findings suggest predominantly positive attitudes from the participants. Based on the results, it seems that teachers deal with a wide range of controversial topics quite frequently, mostly because they take their students’ interest into consideration.